CLINICAL EVALUATION METHODS OF ODONTOGENIC PHLEGMONS IN PEDIATRIC PATIENTS - Akhmedov Ilham Ibrahimovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This  study  explores  the  clinical  characteristics  and  evaluation  methods  of odontogenic  phlegmons  in  pediatric  patients.  Odontogenic  phlegmons—rapidly progressing,  diffuse  purulent  inflammations  of  the  soft  tissues—are  frequently encountered  in  the  maxillofacial  region  of  children  due  to  the  high  prevalence  of untreated dental infections. The immature immune response and anatomical features in  children  often  lead  to  more  rapid  progression  and  higher  risk  of  systemic complications. This article presents findings from a clinical study conducted on 54 pediatric patients aged 3 to 15 years, focusing on the localization, clinical presentation, diagnostic  parameters,  and  assessment  criteria  used  to  classify  the  severity  of  the condition.  Based  on  clinical,  laboratory,  and  radiological  data,  a  comprehensive approach to evaluate and manage odontogenic phlegmons in children is proposed. The implementation of these methods in clinical practice can significantly improve early diagnosis, guide treatment strategies, and reduce complications.